Financial Incentives for Adoption and Kin Guardianship Improve Achievement for Foster Children - David Simon; Aaron Sojourner; Jon Pedersen; Heidi Ombisa Skallet (Institute of Labor Economics (IZA), 2024)
Difference-in-differences analysis of linked administrative data estimates effects of a Minnesota policy change that increased the payments to adoptive parents and kin guardians for children ages 6 and older, making them equal to what foster care payments were, but didn't for younger children. Equalizing payments raised average academic achievement by 31 percent of a standard deviation three years after foster children's cases started, raised the value of payments by about 2,000 per child during this period, raised the monthly chance of moving from foster care to adoption or kin guardianship by 29 percent, improved school stability, and reduced school suspensions.
Keywords: H75; I38; D19; 330; child welfare; education; human capital